Human-animal relationships - Du Toit, Jessica Anne (Department of Philosophy, 2015)
The overwhelming majority of philosophical discussions about the relationships between humans and animals concern the human use and treatment of animals in contexts such as those of food production, scientific experimentation, and pet-keeping. By contrast, the kinds of affective bonds that do - or might conceivably - occur between humans and animals, have received very little philosophical attention. In this dissertation, my main, but not exclusive, concern is with the latter issue. More specifically, I am primarily concerned with the question of whether human-animal relationships can be meaningful. Because pet animals are the clearest candidates for meaningful relationships with us, they will be the focus of my discussion. I argue that at least some human-pet relationships can be meaningful, even if they are not among the most meaningful relationships in our lives. Thereafter, I shall turn to one question about the treatment and use of animals on which the earlier question bears, namely the question of whether the practice of having pets is permissible.